Challenges of branding among public and private universities: the Malaysian context - Shabu, Shahrul Fhaizal; Othman, Azam; Nik Abdul Rahman, Nik Suryani (2015)
Many studies on higher education branding are situated in developed higher education markets such as the US, the UK, and Australia. This work-in-progress paper examines the challenges of higher education branding in the context of Malaysia, a developing higher education market, and argues that public and private university face challenges that are both unique and common in developing and implementing their branding strategy. The findings presented were from on a comparative case study conducted at two (2) Malaysian universities: a government-funded, public institution; and a profit-oriented, private institution. In-depth interviews were conducted with eight (8) key staff from the corporate communication, admission, and marketing departments from the two universities. Among the challenges shared by both types of institutions include the rise of social media, assigning accountability for branding spending, and developing brand coherence throughout the institution. Comparatively, the private university had a more market-oriented perspective of branding, while the public university viewed branding as a way of establishing an identity. The challenges revealed also suggest several important implications for the development of higher education branding strategies and potential directions for future research.